METHOD OF PREPARATIVE SYNTHESIS OF 8-OXO-2'-DEOXYGUANOSINE FOR LABORATORY USING - N. V. Marmiy; D. S. Esipov (Тонкие химические технологии, 2017)
A preparative method for the synthesis of 8-oxo-2'-deoxyguanosine (8-oxo-dG) giving a high yield up to 80% and suitable for laboratory use is suggested. The urgency of the development of this method is associated with the need to obtain large quantities of 8-oxo-dG for the study of biological and pharmaceutical activity. Evidence of this need was obtained in the last decades, when the mechanisms of the interface of DNA repair with intracellular signaling through 8-oxo-dG were discovered and its anti-inflammatory and protective effects were revealed. The suggested method is based on the scheme used to prepare 8-oxo-dG-containing oligonucleotides, but has a number of important modifications. The use of N,N-dimethylformamide as a solvent makes it possible to increase the yield of the nucleophilic substitution reaction and avoid expensive and complicated further purification of silver acetate. Control of the reaction kinetics allows achieving the maximum yield and purity of the product. Alkaline hydrolysis, in contrast to ammonolysis, provides complete and rapid removal of acyl groups, and reversed-phase chromatography on silanized silica gel is an effective and inexpensive method of purification. Such a purification scheme minimizes contamination of the product with residual organic solvents, which is important for biological experiments. From the economic point of view, it is advantageous because of the absence of expensive solvents and the possibility of reusing the carrier. The method makes it possible to obtain pure 8-oxo-dG in preparative amounts and exceeds both its prototype and other existing techniques in the final output. Some intermediate compounds and significant methodological features of the reaction are described.